(untitled) (Simbiótica. Revista Eletrônica, 2020)
Criticism of ideas is a necessary task for the advancement of knowledge. But, for the criticism to be valid, it must start from a precise knowledge, free from misrepresentations, of the ideas that are to be criticized; if not, criticism becomes bad criticism. Morin’s ideas have been subject to bad criticism. This article exposes and discusses one of those bad criticisms: the consideration of Morin’s ideas as a case of biological and physical reductionism. The rigorous exposition of Morin’s ideas shows how this criticism is unfounded and totally misguided. Keywords: Edgar Morin; Criticism; Reductionism; Emergency.